2010
DOI: 10.1002/jso.21767
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of expression of vegf and cox‐2 in nasopharyngeal carcinoma and its association with expression of C‐erbB2 and EGFR

Abstract: Absence of VEGF is a useful indicator of poor prognosis in addition to Cox-2 expression, high stage, and high mitosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 45 publications
2
26
0
Order By: Relevance
“…Finally, we enrolled 15 eligible articles containing survival outcomes [11,[15][16][17][18]22,[24][25][26][27][28][29][30][31][32][33][34][35], among which two studies were written in Chinese [22,33], whereas the others were English articles. These eligible studies were published from 2002 to 2012.…”
Section: Eligible Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, we enrolled 15 eligible articles containing survival outcomes [11,[15][16][17][18]22,[24][25][26][27][28][29][30][31][32][33][34][35], among which two studies were written in Chinese [22,33], whereas the others were English articles. These eligible studies were published from 2002 to 2012.…”
Section: Eligible Studiesmentioning
confidence: 99%
“…Samples from North Asia (China, Korea, Japan, and Singapore) [15][16][17]22,24,25,[27][28][29][30][31][32][33][34] were yielded for HRs. The result suggested that EGFR was associated with NPC prognosis, and HR for OS was 2.05 [1.17, 3.60], (I2 = 92%, P = 0.…”
Section: Subgroup Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…For evaluation of DLL4 and VEGFR-2 expression, a semiquantitative scoring system was developed, which was based on both staining intensity (0, negative; 1, weak; 2, moderate; 3, strong) and percentage of positive cells (0, 0% cells; 1, B25% positive cells; 2, 26-50% positive cells; 3, [50% positive cells). 18,27,28 The 2 scores were added, with a maximum total score of 6. The high expression of a marker, DLL4 or VEGFR-2, was defined as a total score of more than 3.…”
Section: Immunostaining Evaluationmentioning
confidence: 99%
“…Meanwhile, by activating various signal transduction pathways, LMP1 can regulate the expression levels of multiple metastasis related genes, such as E-cadherin, MMPs, c-Met, VEGF, EGFR and COX-2 [69].…”
Section: Mirna and Tumor Angiogenesis Invasion And Migrationmentioning
confidence: 99%